Labour participation and women empowerment: Implications for capacity building of women in potato production in Pakistan - Khan, A.; Dayaram, Kandy; Rola-Rubzen, Maria Fay (2016)
Women occupy a pivotal position in the development discourse. Their importance is not only highlighted by the fact that they constitute more than half of the population but also by virtue of the diverse roles they play in society. Their diversified role ranges from economic contributions of household life to collective societal impact. Women’s work is not limited to a particular field or profession. According to research (National Commission on the Status of Women 2003; World Bank 2007; Food and Agriculture Organization [FAO] 2011) in addition to women’s family roles as mothers, sisters and wives, their participation can be seen in various professions and the workplace. Women constitute a substantial proportion of the work force in Oceania (64 per cent), Sub-Saharan Africa (62 per cent), South Eastern Asia (57 per cent), and South America (59 per cent) (Food and Agriculture Organization [ILO] 2009). Because of their significant contribution, women’s work needs to be integrated into the human development framework. Policy intervention must recognize their potential as agents of growth, which can prove to be helpful in ensuring food security and achieving better living standards for the rural population. Dheepah and Barani (2009), note that while technology, knowledge and education are indicators of welfare and wellbeing of society, development and advancement are indicators of women’s empowerment. Women occupy a pivotal position in the development discourse. Their importance is not only highlighted by the fact that they constitute more than half of the population but also by virtue of the diverse roles they play in society. Their diversified role ranges from economic contributions of household life to collective societal impact. Women’s work is not limited to a particular field or profession. According to research (National Commission on the Status of Women 2003; World Bank 2007; Food and Agriculture Organization [FAO] 2011) in addition to women’s family roles as mothers, sisters and wives, their participation can be seen in various professions and the workplace. Women constitute a substantial proportion of the work force in Oceania (64 per cent), Sub-Saharan Africa (62 per cent), South Eastern Asia (57 per cent), and South America (59 per cent) (Food and Agriculture Organization [ILO] 2009). Because of their significant contribution, women’s work needs to be integrated into the human development framework. Policy intervention must recognize their potential as agents of growth, which can prove to be helpful in ensuring food security and achieving better living standards for the rural population. Dheepah and Barani (2009), note that while technology, knowledge and education are indicators of welfare and wellbeing of society, development and advancement are indicators of women’s empowerment. Women’s work and contribution is particularly important in developing countries such as Pakistan. Whilst women are essentially a part of the social and economic fabric of society, Women’s work and contribution is particularly important in developing countries such as Pakistan. Whilst women are essentially a part of the social and economic fabric of society, their work is not fully acknowledged and recognized. This is more so in a country such as Pakistan where the majority of the population live in rural areas with women constituting half of the rural residents. Agriculture and livestock are the mainstays of Pakistan’s rural economy. Studies undertaken in Pakistan (Amin, Ahmad and Zafar 2009; Nosheen 2011) found a significant correlation between women’s labour participation rates and rural women in the agricultural sector. While women are found to be an integral part of the agricultural production system, their work was rarely recognized. One of the contributory factors is the lack of accurate workforce data and studies on women’s participation and the impact on empowerment. This fact necessitates recognition of women participation and their potential contribution to paid employment which in turn will affect their income levels and empowerment status, improve living standards and ensure food security for rural masses. Thus, it is critical to gain an understanding of women’s labour participation, their levels of development and empowerment in Pakistan. This study examines the participation of women in agriculture in Pakistan and its relationship to empowerment. The following research questions are explored in this chapter: • What are the areas where Pakistani women farmers’ labour participation is most concentrated? • Is there a correlation between women’s labour participation and their empowerment? This study aims to determine the following objectives: 1) Ascertain the role of women in agricultural activities 2) Measure women’s contribution in potato production 3) Ascertain the link between labour participation and women empowerment.